Different ventilatory responses to progressive maximal exercise test performed with either the arms or legs (Clinics, 2011)
OBJECTIVE: This study aimed to compare respiratory responses, focusing on the time-domain variability of ventilatory components during progressive cardiopulmonary exercise tests performed on cycle or arm ergometers. METHODS: The cardiopulmonary exercise tests were conducted on twelve healthy volunteers on either a cycle ergometer or an arm ergometer following a ramp protocol. The time-domain variabilities (the standard deviations and root mean squares of the successive differences) of the minute ventilation, tidal volume and respiratory rate were calculated and normalized to the number of breaths. RESULTS: There were no significant differences in the timing of breathing throughout the exercise when the cycle and arm ergometer measurements were compared. However, the arm exercise time-domain variabilities for the minute ventilation, tidal volume and respiratory rate were significantly greater than the equivalent values obtained during leg exercise. CONCLUSION: Although the type of exercise does not influence the timing of breathing when dynamic arm and leg exercises are compared, it does influence time-domain ventilatory variability of young, healthy individuals. The mechanisms that influence ventilatory variability during exercise remain to be studied.